The Influence of Compaction Methods on the Compressibility Characteristics of Cohesive Soils - Alibrahim, Bashar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Over the past decades, engineers aimed to enhance the engineering properties of natural soil deposits, by compaction to reduce compressibility, permeability and increase bearing capacity. The most common compaction methods used in the laboratory are the Standard Proctor compaction in which, dynamic compaction is performed to obtain compaction characteristics of soils. However, insitu application of most common shallow compaction methods involve the static compaction which is implemented with the use of compaction rollers. The aim of this study is to investigate the influence of compaction method (dynamically and statically) on the engineering properties of selected soils. In order to meet this objective, an extensive laboratory test program is conducted on two selected soils that have significant variation among their plasticities and composition. Various dynamic compaction efforts are conducted at different moisture contents, which are also simulated using static compression. The compacted specimens are tested for measurement of Electrical Resistivity, Undrained Shear Strength and Compressibility characteristics. Results indicate that static compaction reduces the electrical resistivity, and the undrained shear strength. On the other hand, the compressibility and the swelling potential of the compacted specimens are observed to increase when the static compaction is used. The outcomes of this research indicate that field sampling and testing is required for effective design and control of engineering properties of compacted fills, as the method of compaction is observed to have a significant impact on the engineering behavior of soils. Keywords: Static compaction, Dynamic compaction, Compaction efforts, Electrical resistivity, Undrained shear strength, Compressibility.

ÖZ:Son yıllarda mühendisler toprak dolguların zemin emniyet gerilmesini arttırmak amacıyla, toprak yoğunluğunu artırarak geçirimliliği ve sıkışabilirliği azaltmayı hedeflemiştir. Başlıca kompaksiyon (sıkıştırma) yöntemleri, genellikle laboratuarda yürütülen Standart Proctor (dinamik sıkıştırma) testi ve çoğunlukla sahada gerçekleştirilen statik kompaksiyondur. Bu çalışmanın amacı, iki tip kohezyonlu toprak üzerinde farklı iki kompaksiyon yönteminin (dinamik ve statik) etkisini araştırmaktır. Bu amacı gerçekleştirmek için, plastisite indeksleri ve içerikleri arasında önemli farklılıklar bulunan iki tip seçilmiş toprak üzerinde kapsamlı laboratuar deneyleri yapıldı. Çeşitli su muhtevalarında statik ve dinamik kompaksiyon sonuçları karşılaştırılmıştır. Elde edilen numunler üzerinde Elektrik iletkenliği, Drenajsız kayma dayanımını deneyleri uygulanmıştır. Sonuçlar statik kompaksiyon yönteminin, elektrik iletkenliği özelliğini ve drenajsız kayma dayanımını düşürdüğü gözlemlenmiştir. Diğer taraftan şişme ve konsolidasyon özelliklerinin de arttığı gözlemlenmiştir. Bu araştırmanın sonuçları kompaksiyon uygulanan zeminlerin mühendislik özelliklerinin kullanılan yöntemden etkilendiğini ve dolayısı ile araziden numune alımı ve deney yapılmasının gerekliliğini göstermiştir. Anahtar kelimeler: Statik kompaksiyon, Dinamik kompaksiyon, Kompaksiyon enerjisi, Elektriksel iletkenlik, Drenajsız kayma dayanımı, Konsolidasyon.
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Supervisor: Asst. Prof. Dr. Eriş Uygar
Keywords: Soil Mechanics; Static compaction; Dynamic compaction; Compaction efforts; Electrical resistivity; Undrained shear strength; Compressibility